2020
DOI: 10.7150/ijbs.41293
|View full text |Cite
|
Sign up to set email alerts
|

Potential Crosstalk between Liver and Extra-liver Organs in Mouse Models of Acute Liver Injury

Abstract: Carbon tetrachloride (CCl4), Concanavalin A (ConA), bile duct ligation (BDL), and liver resection (LR) are four types of commonly used mouse models of acute liver injury. However, these four models belong to different types of liver cell damage while their application situations are often confounded. In addition, the systematic changes of multiple extra-liver organs after acute liver injury and the crosstalk between liver and extra-liver organs remain unclear. Here, we aim to map the morphological, metabolomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…), and the central nervous system controls energy balance to regulate obesity and fatty liver (290). Moreover, in other liver diseases such as ALI, viral hepatitis, and HCC, the presence of crosstalk between the liver and peripheral organs has been demonstrated (294)(295)(296). These suggest that the crosstalk between the liver and other organs plays a key role in the pathogenesis of liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…), and the central nervous system controls energy balance to regulate obesity and fatty liver (290). Moreover, in other liver diseases such as ALI, viral hepatitis, and HCC, the presence of crosstalk between the liver and peripheral organs has been demonstrated (294)(295)(296). These suggest that the crosstalk between the liver and other organs plays a key role in the pathogenesis of liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…The same experimental results were achieved in the subsequent mouse liver injury imaging experiments. 46 The results of the experiment showed that SSR-LDs has potential to be used in the diagnosis of liver diseases.…”
Section: Fluorescence Imaging Of the Probe Ssr-lds In Vitro Tissue An...mentioning
confidence: 97%
“…Acute liver injury is a serious inflammatory disease caused by various hepatotoxic factors, such as viral infection, improper drug use, excessive ethanol intake, radiation and hepatic surgery. 54 The occurrence and development of acute liver injury is an extremely complex and dynamic process, involving various cells and inflammatory factors. 55 Given that macrophages can initiate inflammation and promote tissue repair, they are considered a 'cornerstone' in acute liver injury.…”
Section: Tam Recep Tor S In Acute Liver Inj U Rymentioning
confidence: 99%